High mortality during tuberculosis treatment does not indicate long diagnostic delays in Vietnam: a cohort study - Sy Dinh N; Co Nguyen V; Duong Bui D; Huong Nguyen T; Vree Marleen; Cobelens Frank G; Borgdorff Martien W (BMC, 2007)
Abstract Background Delay in tuberculosis diagnosis and treatment initiation may increase disease severity and mortality. In evaluations of tuberculosis control programmes high fatality rates during tuberculosis treatment, are used as an indicator of long delays in low HIV-prevalence settings. However, data for this presumed association between delay and fatality are lacking. We assessed the association between diagnostic delay and mortality of new smear-positive pulmonary tuberculosis patients in Vietnam. Methods Follow-up of a patient cohort included in a survey of diagnostic delay in 70 randomly selected districts. Data on diagnosis and treatment were extracted from routine registers. Patients who had died during the course of treatment were compared to those with reported cure, completed treatment or failure (survivors). Results Complete data were available for 1881/2093 (89.9%) patients, of whom 82 (4.4%) had died. Fatality was 4.5% for patients with ≤ 4 weeks delay, 5.0% for 5- ≤ 8 weeks delay (aOR 1.11, 95%CI 0.67-1.84) and 3.2% for > 9 weeks delay (aOR 0.69, 95%CI 0.37-1.30). Fatality tended to decline with increasing delay but this was not significant. Fatality was not associated with median diagnostic delay at district level (Spearman's rho = -0.08, P = 0.5). Conclusion Diagnostic delay is not associated with treatment mortality in Vietnam at individual nor district level, suggesting that high case fatality should not be used as an indicator of long diagnostic delay in national tuberculosis programmes.